2020
DOI: 10.1021/jacs.9b12930
|View full text |Cite
|
Sign up to set email alerts
|

Boronate Ester Bullvalenes

Abstract: Boronate ester bullvalenes are now accessible in two to four operationally simple steps. This unlocks late-stage diversification through Suzuki cross-coupling reactions to give mono-, di-, and trisubstituted bullvalenes. Moreover, a linchpin strategy enables preprogrammed installation of two different substituents. Analysis of solution phase isomer distributions and singlecrystal X-ray structures reveals that isomer preference in the crystal lattice is due to general shape selectivity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…Our group recently introduced a two-step method for the synthesis of substituted bullvalenes from cyclooctatetraene through cobalt-catalyzed [6 + 2] cycloadditions with alkynes followed by photochemical di-π-methane rearrangement . Importantly, this could be extended to incorporate boronate ester functionality, leading to versatile synthetic building blocks …”
mentioning
confidence: 99%
“…Our group recently introduced a two-step method for the synthesis of substituted bullvalenes from cyclooctatetraene through cobalt-catalyzed [6 + 2] cycloadditions with alkynes followed by photochemical di-π-methane rearrangement . Importantly, this could be extended to incorporate boronate ester functionality, leading to versatile synthetic building blocks …”
mentioning
confidence: 99%
“…A recent revival of interest has been led by Bode, [3] Echavarren, [4] and one of our laboratories [5] . In a recent report, we developed easy synthetic access to a range of diaryl substituted bullvalenes [5c] …”
Section: Figurementioning
confidence: 99%
“…The conceivable complexity of this M 2 L 4 system is built upon the reaction graph of the bullvalene ligand. For disubstituted bullvalene networks of this type, there are 15 possible isomers including three enantiomer pairs, (Figure 3b) where nodes represent isomers and edges Cope rearrangement pathways [5c] . For bis‐3‐pyridyl bullvalene there are three populated isomers, A, B, and C, that rapidly interconvert through a lower energy circuit including intermediate isomer D. Isomer C also possesses a degenerate rearrangement pathway with itself (Figure 3b).…”
Section: Figurementioning
confidence: 99%
“…Thus, the reaction appears to be uxional/shape-shiing at room temperature. [36][37][38][39][40] For this substrate, we also modelled the dissociative pathway (Scheme 2D). It was found that bond breakage to two allylic radical intermediates is a higher energy process than the concerted transition state (Scheme 2C vs. Scheme 2D).…”
mentioning
confidence: 99%